Reconstruction of lingual sulcus in a severely atrophic mandible using a modified approach as a pre‐prosthetic surgery: Case series. Issue 2 (23rd February 2022) - Mohseni Salehi Monfared, Seyed Hossein; Shirani, Gholamreza; Moslemi, Neda; Noori, Faranak; Raee, Amir
Abstract: Shallow lingual vestibule and lack of keratinized attached mucosa are considered risk factors for the long‐term success of dental implants. This article describes a modified surgical approach accompanied by a free gingival graft to correct the shallow lingual/buccal vestibule and to increase the keratinized tissue around dental implants. Abstract : The lingual sulcoplasty using the button‐suture technique might be considered for reconstructing the lingual vestibular depth in patients with severe mandibular ridge resorption.